2004
DOI: 10.1128/jcm.42.1.426-430.2004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Human Immunodeficiency Virus Drug Resistance Mutations and Subtypes in Drug-Naive, Infected Individuals in the Army Health Service of Rio de Janeiro, Brazil

Abstract: The prevalence of mutations that confer resistance to antiretroviral drugs was examined in 56 drug-naive, human immunodeficiency virus type 1 (HIV-1)-infected individuals from the Army Health Service in Rio de Janeiro, Brazil. No primary protease inhibitor mutations were found, but secondary mutations were observed in 51.2% of the samples. Fourteen percent of the viruses had reverse transcriptase inhibitor-associated mutations. Comparative analysis of protease secondary mutations from four different time perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
35
0
3

Year Published

2007
2007
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 45 publications
4
35
0
3
Order By: Relevance
“…Additionally, we present the first molecular evidence of horizontal transmission of subtype CRF02_AG in Brazil. This is a rare HIV-1 variant in the country and only two cases have been published in peerreviewed journals (both from the metropolitan area of Rio de Janeiro) (Pires et al 2004, Couto-Fernandez et al 2005. However, the recent identification of novel cases of HIV-1 infection due to CRF02_AG at our laboratory (unpublished observations) suggests that this might prove to be an emerging lineage in the city of Rio de Janeiro.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Additionally, we present the first molecular evidence of horizontal transmission of subtype CRF02_AG in Brazil. This is a rare HIV-1 variant in the country and only two cases have been published in peerreviewed journals (both from the metropolitan area of Rio de Janeiro) (Pires et al 2004, Couto-Fernandez et al 2005. However, the recent identification of novel cases of HIV-1 infection due to CRF02_AG at our laboratory (unpublished observations) suggests that this might prove to be an emerging lineage in the city of Rio de Janeiro.…”
Section: Discussionmentioning
confidence: 87%
“…In Brazil, molecular analyses of HIV-1 nucleotide sequences have shown an epidemic driven mainly by three group M subtypes: B, C, and subsubtype F1 (heretofore designated subtype F1), as well as a myriad of unique BF1 intersubtype recombinants (Morgado et al 1998, Tanuri et al 1999, Vicente et al 2000, Soares et al 2003. Isolated cases of other subtypes, such as subtype D (Morgado et al 1998, CoutoFernandez et al 2006, subtype A (Caride et al 2000), CRF02_AG (Pires et al 2004, Couto-Fernandez et al 2005, CRF28_BF and CRF29_BF (De Sa Filho et al 2006) have also been reported.…”
mentioning
confidence: 99%
“…An increasing number of communications have shown that these compensatory mutations can occur spontaneously in the genome of viruses belonging to subtypes other than B isolated from untreated patients. 18,19 It is not clear if the high frequency of these mutations may contribute to a more rapid crossing of the genetic resistance barrier; however, their existence in HIV-1 strains of naive patients might favor a more rapid evolution toward resistance when additional mutations are selected under therapy.…”
mentioning
confidence: 99%
“…Strain 06BRSAP30 presented the T69N mutation, which poses potential lowlevel resistance to several NRTI (Winters & Merigan 2001). This mutation is by far the most common nonaspartic acid change at codon 69 (Winters & Merigan 2001) and has also been reported from drug-naïve Brazilian patients (Pires et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Up to the present time, this seems not to be the case in Brazil . When compared to figures reported from developed nations, most studies from Brazil have found relatively low rates of primary HIV-1 drug resistance (Brindeiro et al 1999, Dumans et al 2002, Brindeiro et al 2003, Pires et al 2004, Brigido et al 2005, Barreto et al 2006, Medeiros et al 2006, Rodrigues et al 2006, SaFerreira et al 2007, even though isolated surveys recently reported worrisome rates in the port cities of Santos (Sucupira et al 2007) and Salvador (Pedroso et al 2007). Also, resistance rates in Brazil are being reported from studies primarily based in large urban centers and little is known about the prevalence of resistant strains in innermost parts of the country.…”
mentioning
confidence: 99%